2010
DOI: 10.3989/scimar.2011.75n2379
|View full text |Cite
|
Sign up to set email alerts
|

Size-fractionated phytoplankton biomass and production in the tropical Atlantic

Abstract: SUMMARY: Two meridional transects were conducted in the tropical and subtropical Atlantic to describe (i) the spatial variability of total and size-fractionated (picophytoplankton and phytoplankton >2 mm) chlorophyll a (chl a) concentration and primary production, (ii) the relative contribution of each phytoplankton size fraction to total biomass and carbon fixation, and (iii) the spatial variability of size-fractionated phytoplankton growth rate (P/B) and assimilation number (P/chl a) in the ocean. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…[18], [43], [44]). Also, similar phytoplankton growth rates have been reported in the Subtropical Pacific using the 14 C method [45], [46], although the rates reported here were greater than most of the 14 C estimates reported in the NAST-E region [47], [48], [49]. Consequently, our pNPP estimates were also higher.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[18], [43], [44]). Also, similar phytoplankton growth rates have been reported in the Subtropical Pacific using the 14 C method [45], [46], although the rates reported here were greater than most of the 14 C estimates reported in the NAST-E region [47], [48], [49]. Consequently, our pNPP estimates were also higher.…”
Section: Discussionsupporting
confidence: 85%
“…Slightly higher metabolic rates for the large phytoplankton were also reached in these latitudes by using the 14 C method [50], although similar [48], or even lower rates [49] were observed using the 14 C method too. McCarthy and Goldman [53] suggested the existence of microscale nutrient patches resulting from zooplankton excretion and degradation of particulate organic matter.…”
Section: Discussionmentioning
confidence: 61%
“…However, nano-and pico-phytoplankton appear to have relatively low biomass at station L4 (Tarran and Bruun, 2015), but significantly higher photosynthetic efficiency likely yielding higher photosynthetic rates (Barnes et al, 2014). Previous studies have reported pico-phytoplankton biomass and production to be consistently low and much less variable than larger size classes (Uitz et al, 2010), only contributing high proportions of productivity in oligotrophic gyres (Maranon et al, 2001;Moreno-Ostos et al, 2011). Nano-phytoplankton on the other hand often enhance production particularly in coastal upwelling regions (Hirata et al, 2009;Tilstone et al, 1999), due to a higher efficiency of light utilisation (Tilstone et al, 1999).…”
Section: Dependence Of Primary Production On Phytoplankton Community mentioning
confidence: 95%
“…Plankton community structure is variable across space (tens of meters to ocean basins) and time (hours to decadal time scales), and may be a major factor determining the magnitudes of production rates and carbon export, and thus the efficiency of the biological carbon pump in sequestering carbon to the deep ocean [Karl et al 2001, 2012, Vaillancourt et al 2003, Richardson and Jackson 2007, Henson et al 2012. Investigators have described correlations of community structures with patterns of primary production and carbon export in a variety of nutrient regimes [Pollard et al 2009, Moreno-Ostos et al 2011, Cassar et al 2015. Transition regions at gyre edges between higher and lower nutrient regimes can be zones of high biomass and intensified production , Ostle et al 2015 with unique phytoplankton communities distinct from the regions to either side [Kavanaugh et al 2014a, Palevsky et al 2013, Ribalet et al 2010.…”
Section: Introductionmentioning
confidence: 99%